Susceptibilities to antibiotics and antiseptics of new species of the family Enterobacteriaceae. - Freney, J (1988)
One hundred and sixty-nine strains of new species of the family Enterobacteriaceae, isolated mainly from the environment, were tested to determine their susceptibilities to 13 antibiotics and 4 antiseptics or disinfectants. All the species were susceptible to aminoglycosides, doxycycline, and trimethoprim but were resistant to chloramphenicol. Susceptibility to beta-lactams varied more among the strains. However, all the strains were cefotaxime susceptible, apart from some Buttiauxella agrestis strains for which MICs were greater than 256 micrograms/ml. The antiseptic MBCs were similar to those published elsewhere for species of the Enterobacteriaceae of clinical origin. No resistance to chlorhexidine was observed. On the other hand, the environmental strains presented a greater resistance to active chlorine than did the reference strains.